SYNTHESIS AND CHARACTERIZATION OF THE ALIPHATIC PROLINE ESTER AS CORROSION INHIBITOR TOWARDS CARBON STEEL - Handayani (NIM 105 03 048), Nurrahmi
ABSTRACT: The loss caused by corrosion has been motivating the scientists to develop the organic compounds based corrosion inhibitors. One of organic compounds that can be used as corrosion inhibitor is proline, because it has carboxylic group and amine group at pyrrolidine ring. The improvement in corrosion inhibition ability of proline could be achieved by the esterification reaction of proline with the alcohol utilizing SOCl2 (thionil chloride) as activator. In this research, the synthesis of some aliphatic ester proline has been succeeded, which can be used to determine the influence of chain elongation towards corrosion inhibition ability. The products of synthesis are hygroscopic compounds for the methyl proline ester, ethyl proline ester, and propyl proline ester, on the other hand butyl proline ester is liquid. The purification of the synthesized products utilized column chromatography generating the yield of products within interval of 4% - 36%. The characterization of product utilized infrared (IR) and NMR spectrometry. Based on the IR spectrums, all of the synthesized products showed secondary amine peaks as proline, and also showed new specific ester peaks, that different from proline, at wave numbers of 1743-1748 cm -1 and 1242-1260 cm -1. On the other hand, the intensity of C=O carboxylic absorption at wavenumber of 1600 cm-1 decreased. The NMR spectrums showed peaks that suitable to aliphatic proline ester structure. According to IR and NMR spectroscopy data, the synthesized compounds refers to aliphatic proline ester. The results of electrochemical measurements utilizing Tafel method generating the value of % corrosion inhibition as follows: 56.29%; 54.69%; 56.14%; and 57.16% represented methyl proline ester, ethyl proline ester, propyl proline ester, and butyl proline ester, respectively. The results of this research indicate that the elongation chain of aliphatic system give no significant influence towards corrosion inhibition ability of proline ester.